90° PA enhancements of suprathermal electrons near interplanetary shocks - Kajdič, Primož; Lavraud, Benoit; Blanco-Cano, Xóchitl; Sauvaud, Jean-Andre; Arnaud Zaslavsky, Arnaud Zaslavsky; Opitz, Andrea; K. Jian, Lan; T. Russell, Christopher; G. Luhmann, Janet; Maksimovic, Milan (Anali PAZU, 2022)
In this letter we report the results of the first systematic study of a population of suprathermal electrons in the solar wind, called the 90° pitch angle enhancements. This feature was found in the vicinity of interplanetary shocks. We analyzed 2 hours time intervals centered on the shocks. The enhancements were found at 114 of 232 shocks (49 %), which means that this is a common feature. Statistical analysis of shock properties show no important differences between the shocks associated with the enhancements and those not associated with them. Preliminary analysis of electric field fluctuations revealed possible correlation between the presence of 90° PA enhancements of suprathermal electrons and the wave activity.
Keywords: interplanetary shocks; suprathermal electrons; 90° PA enhancements